College algebra - Villa, Normita A.; Marquez, Paz J.; Andrada, Corazon J.; Usona, Laurence P.; Dechavez, Wilma L.; Zarco, Michael L. (Pasig City, Philippines : UNLAD Publishing House, 2008)
This book has been written with the learner in mind. The concepts, follow-up explanations and application exercises are logically presented to maximize students' understanding and learning.
Chapter 1. Sets and the real number system -- Chapter 2. Algebraic expressions -- Chapter 3. Special products and factoring -- Chapter 4. Algebraic fractions -- Chapter 5. Power, roots and radicals -- Chapter 6. Linear equations -- Chapter 7. Problem solving involving linear equations -- Chapter 8. Functions and graphs -- Chapter 9. Quadratic equations -- Chapter 10. Inequalities -- Chapter 11. Variation -- Chapter 12. Sequences and series -- Chapter 13. Binomial Theorem -- Chapter 14. Partial fractions.
Includes bibliographical references.
Keywords: ALGEBRA -- MATHEMATICS